(untitled) (American & British Studies Annual, 2022)
The present article examines the notions of fantasy, illusion and logic in Keats’s romance Lamia (1819) from the perspective of the aesthetic and literary category of the grotesque. In his text Keats puts the grotesque to two uses. First, it serves to mark his ambiguous attitude to both reason and imagination as two exclusive modes of cognition; secondly, it records his uneasiness in relation to the romantic ideal of love. Two conflicting points of view inform and battle in the poem: one might be called Romantic, as it endorses imagination and beauty as values per se; the other invites an interrogation of the idealistic approach. Neither of these two perspectives is unequivocally applauded in the text, and the Romantic grotesque appears a perfect vehicle for expressing this incongruity.